Mahalaga ako personal safety kit an exploration of the use of an educational kit on personal safety skills for the prevention of child sexual abuse to be used by parents educating children between ages 6-8 in Bagong Silang, Caloocan City - Gipa, Shellette; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
There is a presumption that children are vulnerable, passive, weak, and incapable and have diminished the capacity to survive on their own. This attitude tends to neglect and rob the rights of the children especially the sexually abused survivors to live, transform, and actualize to persons of great potential (Song, 2007). It is important for children at an early age to begin understanding that they have certain rights that other people should respect. These rights include the right to self-esteem and privacy, to resist other people's behaviors that are deemed uncomfortable and unwanted situations, to have assertiveness in telling about and to expect help from trusted adults when they experience violence or abuse from others. And the best way to prevent abuse is always education. Parents, as the children's first teachers, play a crucial role in the process of helping children participate for their own protection. They have the responsibility to prevent and teach their children about personal safety skills to avoid any form of abuse.

Mahalaga ako!TM personal safety kit is a personal safety kit which aims to teach about personal safety skills to children for the prevention of child sexual abuse. This kit was designed for parents to teach their children age-appropriate information and skills against child sexual abuse. Overall, Mahalaga ako!TM personal safety kit aims to guide parents to discuss age-appropriate information and personal safety skills in a non-threatening way but also empowers their children to build their self-esteem to increase protective behaviors.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 258-262
Keywords: Sex crimes; Child sexual abuse; Child sexual abuse -- Prevention; Personal safety kit